Case Report: Novel treatment approach for severe interstitial lung disease in type 3 Gaucher disease - Gragnaniello, Vincenza; Carraro, Silvia; Zangardi, Tiziana; Cazzorla, Chiara; Gueraldi, Daniela; Burlina, Alberto B. (Frontiers in Pediatrics, 2025)
Gaucher Disease Type 3 (GD3) is a rare lysosomal storage disorder characterized by both visceral and neurological involvement. Pulmonary manifestations can significantly impact prognosis and quality of life. This case report highlights the challenges in managing severe pulmonary involvement in GD and explores novel treatment approaches. We present a case of a patient with GD3, diagnosed through neonatal screening, who developed severe lung disease despite early initiation of enzyme replacement therapy (ERT). The patient, carrying compound heterozygous variants in the GBA1 gene (p.Leu483Pro, [p.His294Gln + p.Asp448His]), experienced respiratory distress requiring oxygen therapy from the age of 4 months. High-resolution computed tomography revealed a typical interstitial lung disease pattern. Despite ERT and a marked reduction in storage biomarkers, pulmonary symptoms persisted, accompanied by elevated inflammatory markers. We implemented a treatment regimen of systemic corticosteroids followed by hydroxychloroquine, resulting in clinical improvement. Furthermore, we observed a decrease in inflammatory biomarkers, such as TNF-alpha and Pp38 MAPK levels, providing insights into possible pathogenic mechanisms. This case underscores the limitations of ERT in addressing pulmonary manifestations of GD and highlights the need for personalized treatment strategies. It also emphasizes the importance of further research into the pathogenesis of pulmonary damage in Gaucher disease to develop more effective therapies for these challenging cases. The positive response to anti-inflammatory and immunomodulatory therapies suggests a potential role for these approaches in managing GD-related lung disease.